School Principal Leadership in Adiwiyata School Development Using the Planning, Organizing, Actuating, and Controlling Management Framework - Caryati, Caryati; Soedjono, Soedjono; Kusumaningsih, Widya (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study explores how the school principal contributes to the development of an Adiwiyata School through the application of the POAC management framework, which includes planning, organizing, actuating, and controlling, at SD Negeri 05 Beji, Taman District, Pemalang Regency. A qualitative descriptive approach was employed to gain a comprehensive understanding of leadership practices in the implementation of environmental education programs. Data were collected through observations, interviews, and document analysis involving the principal, teachers, and other school stakeholders directly engaged in the Adiwiyata program. The findings reveal that the principal plays a central role in shaping the school’s environmental management strategy. In the planning stage, environmental priorities are integrated into school policies and operational programs. In organizing, clear responsibilities are assigned through the establishment of a dedicated Adiwiyata team. During implementation, the principal encourages collaboration, motivation, and active participation among teachers, students, and the wider school community. Continuous supervision and evaluation further support program consistency and long-term sustainability. These findings suggest that the success of Adiwiyata development depends not only on infrastructure or formal policy, but also on the principal’s leadership capacity to foster collective commitment toward environmental responsibility within the school community.